Photodegradation of organic compounds from Titanates: a review - Loureiro, Sthéfany Nunes; Druzian, Daniel Moro; Oviedo, Leandro Rodrigues; Lourenço, Joana Bratz; da Silva, William Leonardo (Disciplinarum Scientia | Naturais e Tecnológicas, 2023)
Contamination of wastewater for dyes; such as Rhodamine B (RhB), Methylene Blue (MB), and Methyl Orange (MO), has caused environmental problems, such as an imbalance in the aquatic ecosystem and a decrease in photosynthetic activity. Thus, for the treatment of waste in water, advanced oxidative process (AOPs) is used, such as the heterogeneous photocatalysis, in which they have been used in the photodegradation of organic pollutants, enabling the use of alternative materials (nanocatalysts). Titanates (TiO2X) have optical-electronic properties, such as the absorption of a wide range of light and semiconductor behavior, presenting catalytic activity. The analysis of this review in the ScienceDirect and Scopus databases (2017 - Nov 2022) allowed us to demonstrate the different types of titanates with Al+2, Bi+4, Na+2, and W+4 ions for photodegradation of dyes resulting in high percentages of degradation (>80%) mainly due to the formation of free radicals ((•OH) and (•O)) causing oxidation processes in organic compounds. Moreover, properties directly affected the degradation results, such as surface area (allowing an increase in interactions with organic compounds) and band gap energy (allowing the application under visible light). The tendency is that different types of titanates (with metallic ions) are more researched and investigated mainly for photocatalytic applications, allowing the understanding of the synergism mechanism between Ti and metallic ions, to meet sustainable development and the generation of clean energy.